Pengaruh Word Of Mouth, Harga, dan Kualitas Produk Terhadap Keputusan Pembelian Produk di Abadi Digital Printing Kota Kediri - Vrisca Falelia M; Baju Pramuntoko; Agung Pambudi Mahaputra (Jurnal Ekonomi, Bisnis dan Manajemen, 2023)
This research aims to analyze the influence of word of mouth, price and product quality on product purchasing decisions at Abadi Digital Printing, Kediri City. This type of research is quantitative research. The sampling technique in this research was using the Accidental Sampling method. This research uses analytical techniques of validity test, reliability test, correlation coefficient test (R), multiple linear regression test, T test, and F test. The results of the research show that there is an influence of word of mouth, price, and product quality on product purchasing decisions in eternal digital printing in the city of Kediri.